Drug induced bullous fixed drug eruption: a case report - Emperumal, Tamil Selvi (International Journal of Basic & Clinical Pharmacology, 2024)
Bullous fixed drug eruption, which is a cutaneous adverse drug reaction, is commonly seen with antimicrobials and analgesics. Bullous drug eruptions are infrequent, but because they pose a challenge both to affected patients and to treating physicians, they are considered to be the most severe cutaneous adverse reactions (SCAR). It is important to recognize these conditions and to differentiate them from other clinical entities involving blister formation. There may be early signs and symptoms that indicate a severe bullous drug eruption even before blisters and erosions of the skin and mucous membranes become obvious. Once the diagnosis is suspected, appropriate diagnostic procedures and adequate management must be initiated. The latter includes identification of the potentially inducing drug, although it should be taken into account that not all cases of bullous eruptions are drug-induced. In cases with drug causality the potentially culprit agent must be withdrawn, while in cases with other aetiology the underlying condition, e.g. an infection, must be treated appropriately. In addition to best supportive care, immunomodulating therapy may be considered. Here we report 64-year-old male with bullous fixed drug eruptions due to doxycycline administration.